Serious Game for Phobia Treatment in Malaysia - Aslina Baharum; Iza Azura Ahmad Bahar; Nur Shahida Ab Fatah; Rozita Ismail; Rozita Hanapi; Noor Fzlinda Fabeil (2018)
Fear is a bad feeling you have when you are in danger or there is something that frightens you. It is right to experience fear but unreasonable and irrational fear is actually a form of anxiety disorder. This is what we called a phobia. There are hundreds of phobias existed in this world. The best way in reducing the fear is to get regular advice and treatment from doctors. However, most people suffered from phobia are reluctant to see doctors. They also hide their fears from others by avoiding situation that will most like induced their phobia. Nowadays, serious games are developed as one of the treatment for those having phobia, although there are few of them. Most of the games have virtual reality or augmented reality elements to boost the effectiveness of the treatment. This paper proposes a serious game to overcome phobia. The objectives of this paper are to develop a serious game using Game Development Process with Scrum and to evaluate the effectiveness of the developed game to overcome the phobia by analyzing the heartbeat of the phobic person. It is hoped that this game will successfully act as an alternative tool in phobia treatment.